5-Aminosalicylic Acid Inhibits Acute Clostridium difficile Toxin A-Induced Colitis in Rats - Steven R. Vigna (Hindawi Limited, 2014)
We tested the hypothesis that 5-aminosalicylic acid (5-ASA) inhibits toxin A-induced generation of colonic leukotriene B4 (LTB4) and toxin A colitis in rats. Isolated colonic segments in anesthetized rats were treated intraluminally with toxin A for 3 hours with or without 30 minutes of pretreatment with either 5-ASA or sulfapyridine and then colonic tissue levels of LTB4 were measured and inflammation was assessed. Separately, sulfasalazine was administered to rats in their drinking water for 5 days, isolated colonic segments were then prepared, toxin A was administered, and inflammation was assessed as before. Pretreatment with 5-ASA inhibited toxin A-induced increased tissue LTB4 concentration in the colon. Sulfasalazine and 5-ASA but not sulfapyridine significantly inhibited toxin A colitis. However, pretreatment with 5-ASA did not protect against direct TRPV1-mediated colitis caused by capsaicin. Toxin A stimulated the release of substance P (SP), and this effect was also inhibited by sulfasalazine and 5-ASA but not by sulfapyridine. Thus, toxin A stimulates colonic LTB4 resulting in activation of TRPV1, release of SP, and colitis. Inhibition of 5-LO by 5-ASA disrupts this pathway and supports the concept that LTB4 activation of TRPV1 plays a role in toxin A colitis.